2023
DOI: 10.33024/mahesa.v3i5.10399
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Indeks Masa Tubuh Ibu Hamil dengan Kejadian Stunting di Desa Oben Kecamatan Nekamese Kabupaten Kupang

Abstract: Toddlers are one of the age groups that are vulnerable to nutritional problems. One of the nutritional problems in toddlers is the chronic nutritional problem that we know today, namely stunting, where stunting itself is characterized by a child's height being shorter than the standard for his age. Basic Health Research Data (Riskesdas) shows that the prevalence of stunting under five in 2018 reached 30.8 percent, which means that one in three under five is stunted. The prevalence of stunting in the province o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…An upper arm circumference of <23.5 cm indicates Chronic Energy Deficiency (CED), which can lead to Intrauterine Growth Retardation (IUGR), and there is a risk of stunting 13 . This finding was consistent with the research of Pratiwi and Jumetan (2023) in the Village of Oben, Kupang, Indonesia, which showed an association between maternal BMI and the occurrence of stunting 14 . Similarly, the study by Dewi et al (2020) asserts that an upper arm circumference <23.5 cm increases the risk of stunting tenfold compared to a normal upper arm circumference 15 .…”
Section: Discussionsupporting
confidence: 93%
“…An upper arm circumference of <23.5 cm indicates Chronic Energy Deficiency (CED), which can lead to Intrauterine Growth Retardation (IUGR), and there is a risk of stunting 13 . This finding was consistent with the research of Pratiwi and Jumetan (2023) in the Village of Oben, Kupang, Indonesia, which showed an association between maternal BMI and the occurrence of stunting 14 . Similarly, the study by Dewi et al (2020) asserts that an upper arm circumference <23.5 cm increases the risk of stunting tenfold compared to a normal upper arm circumference 15 .…”
Section: Discussionsupporting
confidence: 93%